2012
DOI: 10.1111/tri.12012
|View full text |Cite
|
Sign up to set email alerts
|

Living organ donation practices in Europe - results from an online survey

Abstract: Summary In Europe, living organ donation (LOD) is increasingly accepted as a valuable solution to overcome the organ shortage. However, considerable differences exist between European countries regarding frequency, practices and acceptance of donor–recipient relations. As a response, the Coordination Action project ‘Living Organ Donation in Europe’ (http://www.eulod.eu), funded by the Seventh Framework Programme of the European Commission, was initiated. Transplant professionals from 331 European kidney and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 28 publications
1
64
0
2
Order By: Relevance
“…Thus, current practices of pre-transplant living donor evaluations vary considerably among countries and even among transplant centers. 23 Halleck et al conducted a survey among all Eurotransplant centers (7 countries and 61 centers) in 2012. 24 They found that majority of the centers use creatinine clearance (64%) in estimating GFR and radioisotopic techniques (82%) in assessing SFD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, current practices of pre-transplant living donor evaluations vary considerably among countries and even among transplant centers. 23 Halleck et al conducted a survey among all Eurotransplant centers (7 countries and 61 centers) in 2012. 24 They found that majority of the centers use creatinine clearance (64%) in estimating GFR and radioisotopic techniques (82%) in assessing SFD.…”
Section: Discussionmentioning
confidence: 99%
“…We also strongly advocate for a life-long follow up of live kidney donors to minimize the long-term risks and enable early interventions. [7,45] By performing this survey, we aimed to give the transplant community more insight in their policies and attitudes, hopefully leading to an eventual consensus regarding extended criteria donors, and thereby enlarging the donor pool.…”
Section: Discussionmentioning
confidence: 99%
“…[3,6] Unfortunately, the contra-indications vary greatly between transplant centres worldwide, and even nationally. [7] Transplant professionals have the responsibility to perform individual risk calculations to ensure donor safety. Therefore, the choice to accept a potential donor becomes a rather subjective issue.…”
Section: Introductionmentioning
confidence: 99%
“…While more data from longterm follow-up studies are being generated, we also strongly advocate for a life-long follow-up of living kidney donors to minimize the long-term risks and enable early interventions [33,34]. In particular, regular medical surveillance of renal function, proteinuria and blood pressure should be advised.…”
Section: Living Donation From Marginal Donors: An Evolving Conceptmentioning
confidence: 99%